Applied Computer Sciences in Engineering Third Workshop on Engineering Applications, WEA 2016, Bogotá, Colombia, September 21-23, 2016, Revised Selected Papers - Figueroa-García, Juan Carlos; López-Santana, Eduyn Ramiro; Ferro-Escobar, Roberto (Communications in Computer and Information Science, 2016)
This book constitutes the refereed proceedings of the Third Workshop on Engineering Applications, WEA 2016, held in Bogotá, Colombia, in September 2016. The 35 revised full papers presented were carefully reviewed and selected from 128 submissions. The papers are organized in topical sections on computer science; computational intelligence; simulation systems; fuzzy sets and systems; power systems; miscellaneous applications.